A study on the chinese characters learning strategies among non-chinese beginner-level learners in Malaysia's public university: a case study of Universiti Putra Malaysia (UPM) during MCO period and the implementation of ODL / Tay Yang Lian ... [et al.] - Tay, Yang Lian; Chin, Jing Ru; Lim, Zu Ying; Wan Mohd Rashdi, Wan Faridatul Akma (UiTM Cawangan Kedah, 2022)
This study aims to determine the perception of learners in learning Chinese characters during Mandarin's ODL session, identify the learners' ability in recognizing and reading Chinese characters, and associate the above with the deemed effectiveness of various learning strategies applied by learners in learning Chinese characters, especially during Mandarin's ODL sessions. This study discovers that all respondents think that learning Chinese characters is both very important and interesting, which is a positive indication that students have the necessary motivation and initiative to learn characters through methods they deemed effective, which are primarily based on the principle of "prioritizing Chinese characters with Pinyin as auxiliary". Further findings also indicate a strong connection between remembering a character and remembering its pronunciation, in which students show a higher level of self- confidence in their ability to correctly pronounce the characters that they have learned and are able to comprehend the meaning of words and sentences, and therefore improved their ability to type or write out the characters correctly after listening to its pronunciation. In addition, this study deduced that students prefer using more comprehensive Chinese character learning strategies that involve all three elements, which are the phonetic, orthographic and meaning system of a character at once. However, the regression of deemed effectiveness of practice and review strategies particularly on the graphic comprehension and graphic production features, has also reflected a comparatively lower confidence in students to differentiate characters with a similar shape. Therefore, teachers or instructors should provide proper guidance, encouragement and even demonstrations to students that involve various effective learning strategies, to help motivate students to use those strategies frequently and for a long-term period, which aims to enhance and improve their characters learning process and experience.